Crop-livestock interactions in sub-Saharan Africa and their implications for farming systems research - McIntire, John M.; Gryseels, Guido (Cambridge University Press, 1987)
Describes herding and farming environments and the relative importance of crops and livestock in sub-Saharan Africa.